Interaction between biochar particle size and soil salinity levels on soil properties and tomato yield - Zhuqing Wu; Yaqiong Fan; Zhengquan Zhou; Xinmei Hao; Shaozhong Kang (Biochar)
Abstract The enhancement of saline soil yield potential by biochar was well-documented, but the changes brought by biochar particle size on soil properties and crop performance are not well understood. To investigate the changes in soil properties and tomato yield due to biochar particle size under varying salt stress, we conducted a pot experiment in China Northwest’s solar greenhouse. A total of nine treatments were applied, with three different salt amounts of [S0 (no salt), S1 (0.3% dry weight), and S2 (0.6% dry weight)], and three biochar treatments of B0, B1, and B2 (0, 0.5% of large particles and 0.5% of small particles). Adding biochar did not significantly affect the measured soil chemical properties, except for pH, total nitrogen (TN), and Ca2+. Specifically, the addition of biochar significantly increased soil pH and TN, while reduced soil Ca2⁺ content likely due to biochar selective adsorption of Ca2⁺. Biochar particle size had opposite effects on tomato yield under varying salt stress levels. Compared to S0, the yield under B1 was 19.1% and 36.5% higher, whereas under B2, the yield was 33.1% and 44.2% lower for S1 and S2, respectively. Under no salt stress, small-size biochar increased yield by 51.0% compared to B0, largely due to the improved soil water and nutrient status. These results are of great value for developing better strategies for adding biochar with appropriate properties into saline soils to achieve greater productivity gains. Highlights Biochar addition significantly reduced soil Ca2+ by 16.7–37.9%, while there was no significant difference in the other cations. Large-size biochar alleviated salt stress and improved tomato yield by promoting salt leaching and enhancing soil nutrients. Small particle size biochar exacerbated salinity stress and reduced tomato yield under higher salinity treatments. Small particle size biochar boosted tomato yield in soils without salinity stress. Graphical Abstract